(untitled) - Noe, Raymond A. (Boston, MA., 2005)
The Noe book recognizes the broadening role of training in corporate life. It includes chapters related to instructional design and employee development, careers, and career management. The Noe book includes the most up-to-date developments in training research and practice, including the strategic role of training and the use of new technologies (such as web-based instruction) in training. Finally, a training and development book that finds balance between research and real company practice, and does so in a lively and inspiring manner
Keywords: Employees; Training of